SALIVARY NEUTROPHILS LEVEL AS AN INDICATOR OF BONE MARROW ENGRAFTMENT - Pink, Richard; Vondrakova, Jana; Tvrdy, Peter; Michl, Petr; Pazdera, Jindrich; Faber, Edgar; Skoumalova, Ivana; Indrak, Karel (Biomedical papers, 2009)
Aim: The aim of this study was to investigate the neutrophils level in saliva as an adequate alternative to other methods for evaluating the neutrophil engraftment after autologous stem cell transplantation (ASCT) in hemato-oncology.Method: A total of 35 patients treated for non-Hodgkin's lymphoma or multiple myeloma were stomatologically examined before planned high-dose chemotherapy with ASCT. After removal of potential foci of odontogenic infection all the patients underwent transplantation and during the treatment they were monitored for the level of neutrophils in saliva as a possible early indicator of the neutrophil engraftment. Neutrophil levels in saliva were compared to the neutrophil level in blood and to the degree of oral mucositis (the nurses study).Results: An increase of salivary neutrophils in the mouth rinse of > 25 x 10^6/l was identified as an early sign of successful neutrophil engraftment that occurred 1 to 2 days before the rise of neutrophils in peripheral blood (> 0.5 x 10^9/l).Conclusions: Follow-up of neutrophil levels in saliva might be an adequate alternative to other methods for evaluating the neutrophil engraftment after ASCT in hemato-oncology.
Keywords: Oral cavity rinsing/Neutrophils/Autologous peripheral stem cell transplantation